A study on applying group discussion approach to enhanse speaking skills of English for the first year students at An Duong Vocational Middle School = Áp dụng đường hướng thảo luận theo nhóm để phát triển kỹ năng nói cho sinh viên năm thứ nhất tại trường - Tống, Thị Hoàng Hạnh (ĐHNN, 2017)
46 p. + CD-ROM